2023
DOI: 10.1021/acs.jced.2c00769
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Measurement and Modeling of 9-Phenylcarbazole in Various Organic Solvents at Different Temperatures toward Efficient Process Design of Solvent Antisolvent Precipitation

Abstract: 9-Phenylcarbazole (PCz) is widely used for synthesizing functional molecules in display material industry and synthetic crystal industry. This study aimed to gain reliable experimental data for PCz solubility in common organic solvents under atmospheric pressure in the temperature range of 278.15 to 313.15 K. The selected solvents are methanol, ethanol, n-propanol, isopropanol, n-butanol, n-hexane, cyclohexane, acetonitrile, 1,4dioxane, tetrahydrofuran, dichloromethane, and trichloromethane. Evaluating the exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In this study, we employed the isothermal saturation method to determine the solubility of PBD in 12 organic solvents. The method based on UV spectrophotometry to measure the solubility has been validated in several studies reported by our group. , The specific experimental process is as follows: to ensure that the excess solid phase is visible, extra PBD was added to a spiral-capped quartz sample vial filled with solvent and stirred with a magnetic stirrer for 1 h at the specified temperature. After standing for 0.5 h, a syringe was used to remove the supernatant, and the liquid was filtered through a PTFE membrane filter with a pore size of 0.2 μm to produce a saturated solution at the determined temperature.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we employed the isothermal saturation method to determine the solubility of PBD in 12 organic solvents. The method based on UV spectrophotometry to measure the solubility has been validated in several studies reported by our group. , The specific experimental process is as follows: to ensure that the excess solid phase is visible, extra PBD was added to a spiral-capped quartz sample vial filled with solvent and stirred with a magnetic stirrer for 1 h at the specified temperature. After standing for 0.5 h, a syringe was used to remove the supernatant, and the liquid was filtered through a PTFE membrane filter with a pore size of 0.2 μm to produce a saturated solution at the determined temperature.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…According to the Ostwald–Freundlich equation, decreasing the particle size of organic materials further to the nanorange has exhibited higher solubility in poor solvents, enabling the applications of high-performance small molecules as ink materials for printing processes in optoelectronic devices. The solubility of materials in various solvents serves as the basis for the solvent–antisolvent method, which is the most straightforward and commonly used approach for preparing nanoparticles. …”
Section: Introductionmentioning
confidence: 99%
“…9-Phenylcarbazole (Figure , C 18 H 13 N, CAS Registry Number: 1150-62-5, MW = 243.31) is widely used for synthesizing functional molecules in display material industry and synthetic crystal industry . Initially, it was researched as an alternative to ethylcarbazole and fluorene for the fabrication of triplet harvesting plastic scintillators .…”
Section: Introductionmentioning
confidence: 99%
“…Initially, it was researched as an alternative to ethylcarbazole and fluorene for the fabrication of triplet harvesting plastic scintillators . However, it soon became clear that 9-phenylcarbazole by itself could be a promising organic scintillation detector . During the past several years, the synthesis and application of carbazole derivatives have been of great interest for the chemists and material scientists because these compounds are quite interesting due to their intrinsic photophysical and redox properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation